Networks of risk: international tourists as a biosecurity pathway into national parks - Hulme, Philip E. (Biological invasions, 2024)
International tourists are recognised as vectors of alien microbes, plants, and animals into protected areas worldwide, either by introducing species from overseas or redistributing alien species within a region. Quantitative estimates of the risk from this introduction pathway have relied on surveys of invasive alien species associated with tourist clothing or transport vectors. In contrast, the large-scale movement of tourists across multiple protected areas within a region has rarely been examined. The New Zealand International Visitor Survey was used to estimate the frequency with which several thousand international travellers visited the nation’s 13 national parks. Trends in international visitor movements were compared immediately prior to the closure of international borders due to the SARS-CoV-2 pandemic and again once the border had reopened. Approximately one-third of international visitors only visited a single national park but over 20% visited five or more. The long tail in the frequency of national parks visited highlights that a small number of tourists pose a greater risk of introducing or moving invasive alien species among different protected areas. European tourists visited more national parks and were more likely to camp or stay in mountain huts while in New Zealand, potentially posing a greater biosecurity risk than other nationalities. The largely montane nature of most national parks imposes a strong bioclimatic filter on alien species establishment and combined with border controls, suggests international tourists pose a greater risk by disseminating already established alien species more widely among and within national parks. Network analyses highlighted geographic clustering of national parks based on tourist movements that might facilitate regional spread of alien species. Greater investment in the education of international tourists about the biosecurity risks they pose through spreading alien species into national parks is needed to address Target 6 of the Global Biodiversity Framework.